2012
DOI: 10.1155/2012/292475
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Evoked Potentials in the Brain after Nonperceptible Optical Stimulation at the Neiguan Acupoint: A Preliminary Report

Abstract: We report on small but reproducible human cerebral evoked potentials after bilateral nonperceptible laser needle (658 nm, 40 mW, 500 μm, 1 Hz) irradiation of the Neiguan acupoint (PC6). The results which are unique in scientific literature were obtained in a 26-year-old female healthy volunteer within a joint study between the Medical University of Graz, the Karl-Franzens University of Graz, and the Graz University of Technology. The findings of the 32-channel evoked potential analysis indicate that exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…However, stimulation of the LI4 acupoint with a metal needle will produce insufferable pain and is accompanied by whole-body reactions. Recently, the laser needle as an alternative method to manual acupuncture has been used in many studies because it is effective not only as a treatment method but also as a research tool [19,20,21]. It can simulate traditional acupoints while also reducing the stress effect resulting from metal needles.…”
Section: Evidence Of Acupoint Lateralitymentioning
confidence: 99%
“…However, stimulation of the LI4 acupoint with a metal needle will produce insufferable pain and is accompanied by whole-body reactions. Recently, the laser needle as an alternative method to manual acupuncture has been used in many studies because it is effective not only as a treatment method but also as a research tool [19,20,21]. It can simulate traditional acupoints while also reducing the stress effect resulting from metal needles.…”
Section: Evidence Of Acupoint Lateralitymentioning
confidence: 99%
“…Beside subjective and objective data that there is also a clear deqi sensation evoked by laser acupuncture, another related study published recently by our group is of particular interest [24]. In this study, we reported small, but reproducible human cerebral evoked potentials after bilateral, nonperceptible laser needle (658 nm, 40 mW, 500  μ m, 1 Hz) irradiation of the Neiguan acupoint (PC6).…”
Section: Deqi Sensation In Laser Acupuncturementioning
confidence: 58%
“…Compared with a metal needle, laser acupuncture does not pierce skin and has always been considered to have no therapeutic effect as well as no evocation of de qi. However, in some study reports published in 2012, researchers have demonstrated that subjects with laser acupuncture also experienced de qi [3234]. On the basis that de qi is the sign of acupuncture efficacy these studies signify that using laser acupuncture as an intervention in the control group may cause underestimation of acupuncture effects.…”
Section: Introductionmentioning
confidence: 99%